INNV-04. A MULTI-INSTITUTIONAL CLINICAL AND MRI REPOSITORY OF NEUROFIBROMATOSIS TYPE 1-ASSOCIATED PERIPHERAL NERVE SHEATH TUMORS. (12th November 2021) - Ly, Ina; Hirbe, Angela; Jordan, Justin; Michaels, Olivia; Kwon, Daniel; Borcherding, Dana; Srihari, Divya; Dombi, Eva; Widemann, Brigitte; Pollard, Kai; Pratilas, Christine; Boswell, Demetrius; et al.
Abstract: BACKGROUND: Individuals with neurofibromatosis type 1 (NF1) frequently have peripheral nerve sheath tumors (PNST), including plexiform neurofibromas (PNF), atypical neurofibromas (ANF), and malignant peripheral nerve sheath tumors (MPNST). These tumors reflect a histologic spectrum from benign to malignant. Various clinical and MRI-based features are proposed as risk factors for MPNST development based on small single-institution studies. A major barrier to study these risk factors is collation and annotation of multi-center serial MRIs. To address this, we created a standardized database of clinical data and longitudinal MRIs from NF1-associated PNST from nine international NF1 referral centers. METHODS: Clinical data from NF1 patients are collected in Research Electronic Data Capture databases housed at Massachusetts General Hospital and Washington University, including demographic information, genotype, disease course, treatment history, and survival. ANF and MPNST require histologic confirmation whereas a diagnosis of PNF can also be made based on clinical/radiographic stability. Longitudinal MRIs predating the histologic diagnosis are uploaded to a HIPAA-compliant cloud-based system. RESULTS: Data from 200 patients (87 females, 113 males) with 217 tumors (75 PNF, 40 ANF, 102 MPNST) have been collected. 280 regional and 108 whole-body MRIs have been identified. Median age at the time of histologic diagnosis is 30 years (range 5-64). All tumors are histologically confirmed except for 6 PNF which remained stable over time. Median follow-up time is 32 months. Of 147 patients with available survival data, 32 (21.7%) have died from MPNST progression; estimated median overall survival is 20 months. CONCLUSIONS: In this ongoing work, we have assembled one of the largest systematically annotated clinical and MRI repositories of NF1-associated PNST from pediatric and adult NF1 patients. The data will be accessible to outside researchers which will promote interdisciplinary and multi-center collaborations. Active efforts include the identification of radiomic MRI features to differentiate between PNF and MPNST.